Pre-hospital anaesthesia and assessment of head injured patients presenting to a UK Helicopter Emergency Medical Service with a high Glasgow Coma Scale: a cohort study. Issue 2 (5th February 2019) - Bootland, Duncan; Rose, Caroline; Barrett, Jack W; Lyon, Richard
Abstract : Objectives: Patients who sustain a head injury but maintain a Glasgow Coma Scale (GCS) of 13–15 may still be suffering from a significant brain injury. We aimed to assess the appropriateness of triage and decision to perform prehospital rapid sequence induction (RSI) in patients attended by a UK Helicopter Emergency Medical Service (HEMS) following head injury. Design: A retrospective cohort study of patients attended by Kent Surrey & Sussex Air Ambulance Trust (KSSAAT) HEMS. Setting: A mixed urban and rural area of 4.5 million people in South East England. Participants: GCS score of 13, 14 or 15 on arrival of the HEMS team and clinical findings suggesting head injury. Patients accompanied by the HEMS team to hospital ('Escorted'), and those that were 'Assisted' but conveyed by the ambulance service were reviewed. No age restrictions to inclusion were set. Primary outcome measure: Significant brain injury. Secondary outcome measure: Recognition of patients requiring prehospital anaesthesia for head injury. Results: Of 517 patients, 321 had adequate follow-up, 69% of these were Escorted, 31% Assisted. There was evidence of intracranial injury in 13.7% of patients and clinically important brain injury in 7.8%. There was no difference in the rate of clinically important brain injury between Escorted and Assisted patients (p=0.46). Nineteen patients required an RSI by the HEMS team and this patient group was significantly more likely to have clinically important brain injury (p=0.04). Conclusion: In patients attended by a UK HEMS service with a head injury and a GCS of 13–15, a small but significant proportion had a clinically important brain injury and a proportion were appropriately recognised as requiring prehospital RSI. For patients deemed not to need a HEMS intervention, differentiating between those with and without clinically important brain injury appears challenging. Level of evidence: V.